2020
DOI: 10.3390/ijms21196978
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 Ameliorates Anti-Glomerular Basement Membrane Glomerulonephritis in Mice

Abstract: Growth differentiation factor 15 (GDF15) is a member of the transforming growth factor-β (TGF-β) cytokine family and an inflammation-associated protein. Here, we investigated the role of GDF15 in murine anti-glomerular basement membrane (GBM) glomerulonephritis. Glomerulonephritis induction in mice induced systemic expression of GDF15. Moreover, we demonstrate the protective effects for GDF15, as GDF15-deficient mice exhibited increased proteinuria with an aggravated crescent formation and mesangial expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…This is in line with previous studies showing that Mcpip1 knockdown aggravates liver IRI in mice [35]. Thus, MCPIP1 acts as a negative regulator of immune responses in the kidney [41,42,[51][52][53]]. Yet, various negative regulators display unique signaling abilities and may function in different cells, processes, and phases of inflammatory response.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with previous studies showing that Mcpip1 knockdown aggravates liver IRI in mice [35]. Thus, MCPIP1 acts as a negative regulator of immune responses in the kidney [41,42,[51][52][53]]. Yet, various negative regulators display unique signaling abilities and may function in different cells, processes, and phases of inflammatory response.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, GDF15-deficient mice showed increased levels of the CXCR3 receptor in activated T cells and increased levels of proteinuria with aggravated crescent formation and mesangial expansion in anti-GBM nephritis. This study suggested that CXCL10/CXCR3-dependent signalling promotes T cell infiltration into the organ during GDF15-regulated acute inflammatory processes [ 34 ]. Thus, GDF15 has important value for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this current Special Edition, thirteen original research articles are presented: twelve in vivo studies in a murine or rat model and one in vitro study [ 3 ]. Seven studies show results from AKI models [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], five from fibrosis models (or CKD models) [ 9 , 11 , 12 , 13 , 14 ] and two from a transplant rejection model [ 4 , 15 ] (two studies used two different in vivo models).…”
mentioning
confidence: 99%
“…Others used an IR model to show that the NOX1-selective inhibition attenuates kidney IR injuries via the downregulation of oxidative stress-mediated kinase signaling [ 8 ] or to investigate the autophagy dynamics during an IR injury, a potential treatment strategy due to removing damaged cells, macromolecules and organelles [ 6 ]. The effect of growth differentiation factor 15 (GDF15) was investigated in a murine model of anti-glomerular basement membrane glomerulonephritis [ 7 ]. The study showed that GDF15 is required for the regulation of T-cell chemotactic chemokines in the kidneys and demonstrated the protective effects of GDF15.…”
mentioning
confidence: 99%
See 1 more Smart Citation